Checking up on Couples—A Meta‐Analysis of the Effect of Assessment and Feedback on Marital Functioning and Individual Mental Health in Couples. (12th August 2016) - Fentz, Hanne N.; Trillingsgaard, Tea
Abstract : The primary aim of the current meta‐analysis was to investigate the overall effect of a relationship checkup (RC), a couple‐oriented assessment, and feedback intervention. Systematic literature searches revealed 12 eligible randomized trials published between 1995 and 2015. Results showed significant overall pre–post effect of an RC on marital functioning (Hedge's g  = 0.20) and individual mental health ( g  = 0.44). The between‐group controlled effect size was significant at postassessment ( g  = 0.23) and up to six‐month follow‐up ( g  = 0.23). Characteristics of the RC format, therapist‐guided versus self‐directed, or the study samples, distressed versus healthy, did not moderate the overall effect of the RC. Thus, our results suggest an RC to improve couples' marital functioning up to six‐month follow‐up, while the effect on individual mental health and repeated delivery of a RC awaits further research.